Evaluation of Workers’ Working Postures based on RULA and MCDM: An Application to a SME Producing Kitchenware in Indonesia - Kurniasih, Indah; Kurniawan, V. Reza Bayu; Kusmendar, Kusmendar (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Currently, it is obvious that occupational health and safety culture in companies is on the rise including a focus on workers’ working postures. However, the implementation of these initiatives tends to be notably deficient, particularly in small and medium-sized enterprises (SMEs). This research aims to introduce a framework for evaluating workers’ working postures taking into account ergonomic factors and other influential factors. In this study, the developed evaluation model was applied to an SME producing kitchenware situated in Indonesia using rapid upper limb assessment (RULA), and the method was combined with multi criteria decision-making (MCDM). There were five criteria identified, namely RULA score (C1), the activity’s level of importance (C2), duration (C3), work station environmental condition (C4), and supportive equipment (C5). These five criteria were considered to evaluate five working postures on the production floor. The result indicated that based on the RULA score, five postures were categorized as high risk. Besides, by considering the criteria, working posture in assembly activity (posture 3) has the highest risk level which requires immediate corrective action. This research is applicable as the evaluation of work posture is assessed by considering ergonomic factors and the level of importance for each activity.